Search for supersymmetry in events with a photon, jets, b-jets, and missing transverse momentum in proton-proton collisions at 13TeV - KAYA, MİTHAT (SPRINGER, 2019)
A search for supersymmetry is presented based on events with at least one photon, jets, and large missing transverse momentum produced in proton-proton collisions at a center-of-mass energy of 13 TeV. The data correspond to an integrated luminosity of 35.9 fb -1 and were recorded at the LHC with the CMS detector in 2016. The analysis characterizes signal-like events by categorizing the data into various signal regions based on the number of jets, the number of b-tagged jets, and the missing transverse momentum. No significant excess of events is observed with respect to the expectations from standard model processes. Limits are placed on the gluino and top squark pair production cross sections using several simplified models of supersymmetric particle production with gauge-mediated supersymmetry breaking. Depending on the model and the mass of the nextto-lightest supersymmetric particle, the production of gluinos with masses as large as 2120 GeV and the production of top squarks with masses as large as 1230 GeV are excluded at 95% confidence level.
Keywords: MODEL; SUPERGRAVITY; EXTENSION; INVARIANT; SQUARK